2003
DOI: 10.1021/jo035355q
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of the Molecular and Chiral Recognition of Cycloalkanols and Camphor by Modified β-Cyclodextrins Possessing Simple Aromatic Tethers

Abstract: The complex stability constants (K(S)) and thermodynamic parameters (DeltaG degrees, DeltaH degrees, and TDeltaS degrees ) for 1:1 inclusion complexation of beta-cyclodextrin (beta-CD) derivatives, 6-O-phenyl-beta-CD (2) 6-O-(4-formyl-phenyl)-beta-CD (3), 6-O-(4-nitrophenyl)-beta-CD (4), 6-O-(4-bromophenyl)-beta-CD (5), 6-O-(4-chlorophenyl)]-beta-CD (6), and 6-O-(4-hydroxybenzoyl)-beta-CD (7) with representative guest molecules, cyclic alcohols (cyclopentanol, cyclohexanol, cycloheptanol, cyclooctanol), (+/-)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 45 publications
1
17
0
1
Order By: Relevance
“…66 Cyclodextrins posses a hydrophobic central cavity and a hydrophilic outer surface and can therefore be used to improve the delivery for poorly soluble drugs. 82 Therefore, in addition to hydrogen bonds, non-polar dispersion is also important.…”
Section: The Test Set Complexesmentioning
confidence: 99%
“…66 Cyclodextrins posses a hydrophobic central cavity and a hydrophilic outer surface and can therefore be used to improve the delivery for poorly soluble drugs. 82 Therefore, in addition to hydrogen bonds, non-polar dispersion is also important.…”
Section: The Test Set Complexesmentioning
confidence: 99%
“…Although the free‐energy difference δΔ G 0 =Δ G 0 (4‐pentylpyridine)−Δ G 0 (4‐methylpyridine) is −10 kJ mol −1 , the enthalpy difference δΔ H 0 =Δ H 0 (4‐pentylpyridine)−Δ H 0 (4‐methylpyridine) is positive and only 1.7 kJ mol −1 ; δ T Δ S 0 = T Δ S 0 (4‐pentylpyridine)− T Δ S 0 (4‐methylpyridine)=11.8 kJ mol −1 at 298 K. Therefore, the tighter binding of 4‐pentylpyridine relative to 4‐methylpyridine can be attributed to the entropic term. Liu et al 14. reported that chiral recognition of camphor by modified cyclodextrins is driven by entropic change.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of mono(6-phenolic-6-deoxy)-β-CD 1 [18] To a solution of phenol (0.4 g, 4 mmol) in DMF (10 mL) is added anhydrous K 2 CO 3 (0.56 g, 4 mmol). The mixture is stirred for 2 h at room temperature under nitrogen, after which 6-OTs-β-CD (1.9 g, 1.5 mmol) in dry DMF (20 mL) is added dropwise with stirring, and then the whole solution is heated at 80℃ for 24 h. The resultant solution is evaporated under reduced pressure to give a yellow powder, which is dissolved in a minimum amount of hot water, and then the solution is poured into acetone (200 mL).…”
Section: 2mentioning
confidence: 99%